Non-glycemic effects of pioglitazone and incretin-based therapies. (October 2013) - Rizzo, Manfredi; Avogaro, Angelo; Montalto, Giuseppe; Rizvi, Ali A
<x xml:space="preserve">Abstract</x> Atherosclerosis and cardiovascular events are highly prevalent and represent the major cause of mortality in patients with type 2 diabetes. Therefore, there is significant interest in the non-glycemic properties of anti-diabetic agents, particularly on those that are effective on cardiovascular risk factors. Thiazolidinediones and incretin-based therapies (IBTs) represent some of the most recent treatment options approved for the management of type 2 diabetes; these agents have shown important glycemic effects, as well as a number of non-glycemic effects. The latter include those on body weight, inflammation, hypertension and dyslipidemia, thus impacting the different components of the metabolic syndrome. Pioglitazone has been shown to significantly reduce cardiovascular adverse outcomes, while preliminary data on IBTs are very encouraging as well. Although highlighting the non-glycemic effects of pioglitazone and incretin-based therapies is of potential significance, clinical practice and patient care must be based largely on evidence-based medicine. Therefore, definitive opinions will await additional data from ongoing studies evaluating the effects of both GLP-1 agonists and DPP-4 inhibitors on cardiovascular morbidity and mortality.